(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Purpose: To assess the clinical and demographic profile of keratoconus(KC) and to evaluate the improvement in visual acuity with specialty contact lenses in patients attending a tertiary eye hospital in south India. Methods: This prospective clinical study included 204 eyes of 102 patients diagnosed as keratoconus attended at contact lens clinic of Regional Institute of Ophthalmology, Trivandrum. A thorough clinical examination was done including slit lamp examination, retinoscopy and Computerised corneal topography. Contact lens trial was done with specialty contact lenses like Rigid gas permeable lens (RGP), RoseK, mini-scleral and scleral lenses and visual acuity was recorded. Results: The mean age of presentation was 24. 27 ± 6.6 with a male predominance and bilateral involvement in 94.12%(96) of cases. Allergic conjunctivitis and eye rubbing are the two important predisposing factors recorded in 61.8%(63) and 65.7%(67) of the study population respectively. The most important clinical sign leading to reference to the tertiary centre was presence of refractive error with visual acuity did not improve to 6/6. Rigid Gas permeable (RGP) lenses were the most commonly prescribed type. Only 68.1%(139) eyes achieved visual acuity LogMAR less than 0.50 with spectacles, while 99%(202) achieved this with contact lenses. No significant association was found between severity of keratoconus and age, sex or eye rubbing. Conclusion: Specialty contact lenses provide a superior visual acuity than spectacles in Keratoconus patients. This study identifies the presence of keratoconus in young adults, the importance of screening for early detection of the disease and the management of ocular surface factors to prevent the progression of ectasia.